-(5x-4y+1)=

Simple and best practice solution for -(5x-4y+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5x-4y+1)= equation:


Simplifying
-1(5x + -4y + 1) = 0

Reorder the terms:
-1(1 + 5x + -4y) = 0
(1 * -1 + 5x * -1 + -4y * -1) = 0
(-1 + -5x + 4y) = 0

Solving
-1 + -5x + 4y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + -5x + 1 + 4y = 0 + 1

Reorder the terms:
-1 + 1 + -5x + 4y = 0 + 1

Combine like terms: -1 + 1 = 0
0 + -5x + 4y = 0 + 1
-5x + 4y = 0 + 1

Combine like terms: 0 + 1 = 1
-5x + 4y = 1

Add '-4y' to each side of the equation.
-5x + 4y + -4y = 1 + -4y

Combine like terms: 4y + -4y = 0
-5x + 0 = 1 + -4y
-5x = 1 + -4y

Divide each side by '-5'.
x = -0.2 + 0.8y

Simplifying
x = -0.2 + 0.8y

See similar equations:

| y^2(3a-4y)=0 | | y[n]+0.5y[n-1]=2x[n-1] | | 5x+1/4+7x-4/9=14 | | 41/20=x+1/(y+1/z) | | -3(4-2x)=18 | | 0y=ox | | 2(x+2)/8=5 | | 111-3x=15x+23 | | 15x-275=6x-5 | | s=2hw+2wh+2hl | | 6x-119=2x-7 | | 24f-16fg= | | y/2+5=16 | | 6w+w+8w= | | 14x-190=4x-10 | | 6w-w+6w= | | 2x+65=7x-10 | | 9-7X=9X+21 | | -126-8x=16x+18 | | 5(3x+5)-4(2x-3)=5x+3(2x+12)+1 | | 11x+8=8x-29 | | 59-4x=32x+15 | | -28X-6X=12-10X | | 14-9x=199-44x | | 3+7x=27+1x | | 11X+22=4X+113 | | 2.16x^2-5.40x-3.24=0 | | 60-x=19 | | x-6/10+x-4/15=x+2/6 | | 12*(x-2)+6*(5-x)=4x-6 | | x^4+12x^3+36x^2-64=0 | | 5w^8-45w^7-50w^6=0 |

Equations solver categories